Use of Field Flexural Demand Data for Reliability-Based Analysis and Design of Concrete Railroad Sleepers - Edwards, J. Riley; Canga Ruiz, Alvaro E.; Bastos, Josué César; Liang, Yubing; Dersch, Marcus S. (Frontiers in Built Environment, 2020)
Concrete is the dominant sleeper material choice for demanding locations on heavy axle load (HAL) freight railroads with steep grades, sharp curves, and high annual gross tonnage. Center flexural cracking is one of the most common factors limiting the service life of concrete sleepers in North America, and rail seat cracking has also been documented as a performance concern. As such, development and implementation of a structural design method that enables optimization of sleeper design for varied applications and loading environments will reduce initial capital cost and recurring maintenance expense. Field instrumentation has been developed to reliably capture revenue service field flexural demands, facilitating a probabilistic design method for the flexural capacity of concrete sleepers with bending data as the primary input. This paper presents a design process based on structural reliability analysis concepts whereby target values for reliability indices (β) for new designs are obtained and compared with existing designs for further design optimization. New (proposed) designs are quite different from current ones. For HAL freight, a reduction in rail seat bending capacity of approximately 40% is justified, reducing the size of the rail seat cross section by approximately the same magnitude. In most cases the proposed designs have fewer prestressing wires and a higher centroid of prestressing steel. In all cases the flexural capacities at the sleeper center and rail seat are better balanced from a structural reliability standpoint.